Automatic Solar panel cleaning system using Arduino - khan, Imran; J. , Mohana (International Journal of Psychosocial Rehabilitation, 2020)
Electricity has been one of the crucial problems the world is aiming at in India; the stockpile of vitality has been one of the serious issues for both downtown and provincial family units. Over 60 to 70 percent of the vitality request of the nation is met by fuel wood and farming deposits. Sun-based vitality is a sustainable wellspring of vitality, which has an incredible thrust, and through the sun it is channeled. A sustainable power source is essential to supplant the utilizing of electric vitality created by oil. Sun-powered power has gotten a wellspring of sustainable power sources, and sun-powered vitality applications ought to be upgraded. The sunlight-based solar photovoltaic module is commonly utilized in grubby conditions; in these cases, it is utilized in India. The dust is available publicly on the solar board's main portion and impedes the illumination from the sun. It decreases the force age limit of the board. The force yield decreases Just about as much as by sun-based board isn't excreted for all the period. The maintenance system was built to scrub the sun-centered panel by regulating the functionality of Arduino as microcontroller unit (MCU). To expel the residue in the sun-oriented boards and to improve the force productivity.